Comparison of Prior Bridging Intravenous Thrombolysis With Direct Endovascular Thrombectomy for Anterior Circulation Large Vessel Occlusion: Systematic Review and Meta-Analysis - Chen, Zhao-Ji; Li, Xiao-Fang; Liang, Cheng-Yu; Cui, Lei; Yang, Li-Qing; Xia, Yan-Min; Cao, Wei; Gao, Bu-Lang (Frontiers in Neurology, 2021)
Background: Whether bridging treatment combining intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT) is superior to direct EVT alone for emergent large vessel occlusion (LVO) in the anterior circulation is unknown. A systematic review and meta-analysis were performed to investigate and assess the effect and safety of bridging treatment vs. direct EVT in patients with LVO in the anterior circulation. Methods: The Pubmed, Embase, and Cochrane library were searched to assess the effect and safety of bridging treatment and direct EVT in LVO. Functional independence, mortality, asymptomatic and symptomatic intracranial hemorrhage (aICH and sICH), and successful recanalization were evaluated. The risk ratio and the 95% CI were analyzed. Results: Among 8 studies included, there was no significant difference in the long-term functional independence (OR=1.008, 95% CI (0.845,1.204), P = 0.926), mortality (OR=1.060 , 95% CI (0.840,1.336 ), P = 0.624), recanalization rate (OR=1.015, 95% CI (0.793,1.300), P = 0.905) and the incidence of sICH(OR= 1.320, 95% CI (0.931,1.870), P = 0.119, Fig.5) between bridging therapy and direct EVT. After adjusting for confounding factors, the bridging therapy showed a lower recanalization rate (effect size or ES=-0.377, 95% CI (-0.684,-0.070), P = 0.016), but there was no significant difference in the long-term functional independence (ES= 0.057, 95% CI (-0.177, 0.291), P = 0.634), mortality (ES=0.693, 95% CI (-0.133, 1.519), P = 0.100) and incidence of sICH (ES= -0.051, 95% CI (-0.687, 0.585), P = 0.875) compared with direct EVT. Meanwhile, in the subgroup analysis of RCT, no significant difference was found in the long-term functional independence(OR=0.927, 95% CI (0.727,1.182), P = 0.539), recanalization rate(OR=1.331, 95% CI (0.948,1.867), P = 0.099), mortality(OR=1.072, 95% CI (0.776,1.481), P = 0.673) and sICH incidence (OR= 1.383, 95% CI (0.806,2.374), P = 0.977) between patients receiving bridging therapy and patients receiving direct DVT. Conclusion: For stroke patients with acute anterior circulation occlusion and eligible for intravenous thrombolysis, there is no significant difference in the clinical effect between direct EVT and bridging therapy, , which needs to be verified by more randomized controlled trials.